Momentum-Based Race Analysis and GRU-Based Predictive Modeling - Zhang, Haoran; Huang, Jirui; Xing, Zhongshi (International Journal of Computer Science and Information Technology, 2025)
This study analyzes the data from the 2023 Wimbledon Men's Tennis Final, defines the concept of "momentum", and constructs a time - series prediction model based on the Gated Recurrent Unit (GRU). The objective is to develop a model capable of precisely capturing the point - by - point dynamic states during the match and presenting them in a visual format. Additionally, it validates the stochastic characteristics of the "momentum" phenomenon and evaluates its influence mechanism on the match trends.